Epidemiological pattern of psoriasis, vitiligo and atopic dermatitis in India: Hospital-based point prevalence - Sorna Kumar; Chitra S Nayak; Tanmay Padhi; Gnaneshwar Rao; Ashwin Rao; V K Sharma; C R Srinivas (Wolters Kluwer Medknow Publications, 2014)
Background: The knowledge of the prevalence of common dermatoses will be useful for optimum use of valuable resources of the country. Aim: The aim of the study is to determine the pattern and prevalence of psoriasis, vitiligo and atopic dermatitis (AD) in India. Materials and Methods: This was a hospital-based study conducted on a single day in one medical college each in four zones of India. Results: The point prevalence of dermatological cases was 9.25%. The point prevalence of psoriasis, vitiligo and AD were 8%, 9.98% and 6.75% respectively. Chronic plaque type psoriasis was the most common (50%) clinical pattern. The most common site of involvement of psoriasis was the palms. Stable type of vitiligo was common which accounted for 65.21%. Lower lip was involved in 75% of mucosal vitiligo. Lower limbs were the most common site of onset of vitiligo. AD was most prevalent in the first decade (40.7%). Personal history of atopy was present in (59.5%) patients. Dry skin was present in 92.5% of patients. Conclusions: Our data correlates with previous hospital-based prevalence studies of psoriasis, vitiligo and AD.